2022
DOI: 10.1177/03080226221097314
|View full text |Cite
|
Sign up to set email alerts
|

Handwriting and typing: Occupational therapy practice when supporting adolescents with handwriting difficulties

Abstract: Introduction While most children have developed effective handwriting by secondary school age, some have handwriting difficulties that hamper academic progress. Occupational therapists play a role in assessment and planning support, which may include introducing typing as an alternative. However, there is limited understanding regarding how decisions are made about recommending typing. This study explored the support provided to adolescents with handwriting difficulties by occupational therapists, and the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…Practitioners suggested that there were student‐level factors, such as age, gender and the presence of additional needs that would be considered in the decision‐making process of whether to persevere with handwriting or offer typing as an alternative. This is similar to the findings reported in a recent study on the work of OTs with secondary school students with handwriting difficulties (Nightingale et al, 2002). OTs described a child‐centred approach to decision‐making around the recommendation of typing, considering motivation, the effect on well‐being and the need for a functional method to record schoolwork.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Practitioners suggested that there were student‐level factors, such as age, gender and the presence of additional needs that would be considered in the decision‐making process of whether to persevere with handwriting or offer typing as an alternative. This is similar to the findings reported in a recent study on the work of OTs with secondary school students with handwriting difficulties (Nightingale et al, 2002). OTs described a child‐centred approach to decision‐making around the recommendation of typing, considering motivation, the effect on well‐being and the need for a functional method to record schoolwork.…”
Section: Discussionsupporting
confidence: 92%
“…This highlights that the transition to typing may not be a ‘one‐size‐fits‐all’ and different students may benefit from particular provision. In addition, as also reported by OTs in Nightingale et al (2002) practitioners in the present study recognised the need to reduce stigma, which may be observed when a student starts to use a word processor and they then feel different to their peers who are still using handwriting in the classroom.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the handwriting process constitutes an important competence and a fundamental starting point in the learning process, rather, it is the common denominator between learning other academic subjects such as reading, writing, and arithmetic [5]. It is the basis of teaching, learning, logical reasoning, and solid observation [6]. The ability to write is the result of both mental and physical development related to the capacity to adapt and transmit signals between the nervous system and the motor systems of the body (muscles) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Handwriting, and related fine motor problems, are a primary reason for referral to occupational therapy, particularly in the school setting. Occupational therapists (OTs) play a significant role in this regard, by offering a variety of services to improve handwriting [ 8 , 9 ]. These services may be delivered directly by assessing the child’s performance (motor, cognition, visual perception, and psychological status) observing, and interviewing and consulting parents and teachers as the primary sources of information about the child’s handwriting problems [ 10 ] for goal setting, planning, and intervention.…”
Section: Introductionmentioning
confidence: 99%